Aquaculture health management : design and operation approaches - Kibenge, Frederick S. B.; Powell, Mark D. (London : Elsevier ; Academic Press, 2020)
"Presents the biosecurity measures used to prevent the spread of disease Discusses fish immunology to help readers understand preventive medicine for a healthy fish production Examines the latest scientific methods and technologies to maximize efficiencies for healthy fish production for farming Includes the most commonly researched fish, crustaceans and mollusks in aquaculture"--
Includes bibliographical references and index.
Keywords: Aquaculture